Perceptions of the sugar-sweetened beverage tax in South Africa: a comparative study - Jankeeparsad, Thanesha Reddy (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
This exploratory, comparative study aimed to investigate perceptions of the participants in the study in South Africa regarding the tax on sugar-sweetened beverages. The study further aimed to compare these perceptions with perceptions identified in selected foreign jurisdictions that have levied the tax on sugar-sweetened beverages. A voluntary, paper-based, anonymous survey questionnaire that included both closed- and open-ended questions was selected as the primary method of data collection. This questionnaire was administered to post-graduate Bachelor of Commerce Accounting and Postgraduate Diploma in Accounting students, aged twenty-one years and older, studying at three residential universities in South Africa, during the 2018 academic year. An extensive analysis of literature available on sugar-sweetened beverage taxes, both locally and internationally, was conducted. The two main constructs (construct 1: perception of the sugar-sweetened beverage tax and the price of sugar-sweetened beverages and construct 2: the social impact of the sugarsweetened beverage tax) were then analysed using descriptive statistics. This study found that there is a significant association between gender and perception that the sugary beverage levy will be beneficial to health, with female perceptions of the benefit of the sugary beverage levy being greater than that of males. Respondents appear to have a positive perception of the sugary beverages levy, understand the sugary beverage levy, as well as the health benefits that will be derived from the levy. Respondents supported the tax on sugar-sweetened beverages if the revenue generated was used to improve the health care system and if the price of healthy foods decreased. Female respondents were found to drink fewer sugarsweetened beverages than male respondents, but females reported higher sugar-sweetened beverage consumption during stressful periods. The current study can possibly provide policy makers with more information regarding acceptance of the sugar-sweetened beverage tax and shape guidelines for future amendments of the tax imposed.
Keywords: Soft drinks -- Taxation -- South Africa; Carbonated drinks -- Taxation -- South Africa; Soft drinks -- Health aspects; College students -- South Africa -- Attitudes